Characterization of DNA Binding Sites of RokB, a ROK-Family Regulator from Streptomyces coelicolor Reveals the RokB Regulon. - Paulina Bekiesch; Karl Forchhammer; Alexander Kristian Apel (PLoS ONE, 2016)
ROK-family proteins have been described to act either as sugar kinases or as transcriptional regulators. Few ROK-family regulators have been characterized so far and most of them are involved in carbon catabolite repression. RokB (Sco6115) has originally been identified in a DNA-affinity capturing approach as a possible regulator of the heterologously expressed novobiocin biosynthetic gene cluster in Streptomyces coelicolor M512. Interestingly, both, the rokB deletion mutants as well as its overexpressing mutants showed significantly reduced novobiocin production in the host strain S.coelicolor M512. We identified the DNA-binding site for RokB in the promoter region of the novobiocin biosynthetic genes novH-novW. It overlaps with the novH start codon which may explain the reduction of novobiocin production caused by overexpression of rokB. Bioinformatic screening coupled with surface plasmon resonance based interaction studies resulted in the discovery of five RokB binding sites within the genome of S. coelicolor. Using the genomic binding sites, a consensus motif for RokB was calculated, which differs slightly from previously determined binding motifs for ROK-family regulators. The annotations of the possible members of the so defined RokB regulon gave hints that RokB might be involved in amino acid metabolism and transport. This hypothesis was supported by feeding experiments with casamino acids and L-tyrosine, which could also explain the reduced novobiocin production in the deletion mutants.